(untitled) (Research, Society and Development, 2021)
The objective of this research was to understand the learning and the pragmatism of students in remote classes determined by Digital Technologies of Information and Communication (DTIC). The research was an exploratory and descriptive. Convenience type sample. An in-depth (semi-structured) interview was conducted and descriptions of the interviews were carried out for the construction of the textual Corpus. The analysis of this textual Corpus was carried out as it follows: i) analysis of the trivia of signs (language - writing, dialectic and rhetoric) of the interviewers ii) lexical analysis, with the assistance of the software called IRAMUTEQ. Initial difficulty in adapting was observed due to the radical change that both students and teachers underwent, however, there are currently signs of adaptation in this new situation when compared to the beginning of isolation at the time of COVID-19. Flexibility is the strength of the classes, as the students report the practicality, even though they describe that there are problems with connection and the lack of interaction between the students-teachers or students-students. Some changes are still needed to offer more effective methods to improve the learning process, as well as resources offered by DTIC.